Redes de educação ambiental : caracterização e desenvolvimento do pólo Maringá - Tavares, Cristiane Montavanelli (2008)
Social networks present as a new perspective to act, organize themselves and form partnerships to meet the social and environmental needs. Networks are strategies for change and traditional hierarchical forms of work, providing the change of models and space for experimentation and learning. The study aimed to characterize the creation of the Network of Environmental Education of Parana, through historical survey of networks of environmental education in Brazil and southem region, in addition to explain the actors involved in the process of construction of the Pole Maringá. Thus, we did eight interviews with educators environmental active participants of this network. The evidence collected in interviews were analyzed using the technique of analysis of Content, to identify the profile of each educator, their goals in the network and its ideas and practices in environmental education. The analysis of the environmental profile of educators participating in the Pole Maringá showed that the group is very diverse. Clearly it is that the different experiences of the participants of Maringa pole inserted in formal education and / or non-formal leverage the exchange of information and knowledge, enriching and promoting the development of projects connected to the network. Through the eight categories of analysis raised was possible to see that the design of networks and environmental practices, submitted by participants of the survey are in line with the Environmental Education critical and emancipatory. It was observed in the speeches of all the interviewees commitment to environmental causes, and the dedication to the principIes of Maringa Pole. For many, the Pole was a way of rediscovering the environmental dimension, a cause for reflection on the practice and teaching environment. It tumed out also that the concepts and practices of environmental educators are clearly different, so necessary to enlarge the debate and the socialization of knowledge. The interviewees showed in their reports the need for an Environmental Education criticism aimed at changing attitudes and values of social elements. So, for the articulation of Maringa Pole can expand it is necessary to invest in projects in communication and disclosure of activities, these factors are essential for the motivation of networking and expansion of various us.